Implementation of Class-Based Storage for Garment Accessories Warehouse Management Using FSN Analysis at PT. XYZ - Jundi Nourfateha Elquthb; Lulu Riesta Nugroho; Annisa Uswatun Khasanah (Journal of Industrial Engineering and Halal Industries, 2024)
A manufacturing company has a close relationship with warehouse operations, which function as centres for storing and managing raw materials and finished products. Proper operational expertise is essential in warehouse management to ensure that all processes within the warehouse run smoothly. The warehouse is a meeting point for various raw materials with different specifications, making it highly susceptible to mismanagement. In this context, several issues have been identified in warehouse management, such as a lack of space or empty shelves, outdated data recording processes, and improper placement of raw materials. An analysis was conducted to identify accessory items in the warehouse based on their similarities using class-based storage to overcome these issues. In this study, the FSN (Fast, Slow, Non-moving) analysis method was used to determine the grouping of garment accessory items based on their production usage and movement in the warehouse. A total of 37 types of accessory items were identified, with the majority, 23 items, classified as fast-moving, indicated by a high turnover rate above 3. The remaining items were categorized as slow-moving and non-moving, with turnover rates below three due to their lower movement. The turnover rate indicates how often or quickly an item moves and is used (enters and exits the warehouse). Thus, several underlying causes of the issues hindering the distribution process in the garment accessories warehouse at PT XYZ were identified. Subsequently, several recommendations were provided for warehouse management, such as improving the layout according to item grouping and conducting regular evaluations to ensure a balanced availability of space and stock. This strategy is crucial for enhancing workers' productivity in the garment accessories warehouse.